Blood levels of dioxins, furans, dioxin-like PCBs, and TEQs in general populations: A review, 1989–2010 - Consonni, Dario; Sindaco, Raffaella; Bertazzi, Pier Alberto (Environment international, 2012)
A comprehensive worldwide literature review of blood levels of dioxins and dioxin-like compounds in non-exposed adult general populations was performed. The studies published in 1989–2010 reporting information on polychlorinated dibenzo-para-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), non-ortho-PCBs (nPCBs), mono-ortho-PCBs (mPCBs) levels and Toxic Equivalencies (TEQs, a summary weighted measure of their combined toxicity) were reviewed. TEQs were calculated using as standard the most recent WHO 2005 reevaluation of Toxic Equivalency Factors (TEFs). Weighted multiple regression analyses adjusted for year, subject's age, type of sample analyzed, method used for values below detection limit, and central tendency measure used were performed for each congener and standardized TEQs (log-transformed). We identified 187 studies regarding 29,687 subjects of 26 countries. Year of blood collection ranged from 1985 to 2008. The studies reporting congener levels 161. In adjusted analyses, European countries showed higher levels of most dioxin-like congeners and TEQs. A strong positive association of subjects' age with most congeners and with TEQ values was found, confirming previous findings. Significant decreases over time (1985–2008) were documented for PCCDs, PCDFs, and TEQs including their contributions. No significant decrease was found for non-ortho-PCBs, notably PCB 126. Only some mono-ortho-PCBs showed clear significant declines. Accordingly, TEQs including only PCB contribution did not decrease over time. In interpreting these findings, it should be considered that for dioxin-like PCBs the analysis period was shorter (17years), since these compounds were first measured in 1992.